2005
DOI: 10.1158/0008-5472.can-04-2085
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Infidelity and Centrosome Duplication Errors in Cells Overexpressing Tripeptidyl-Peptidase II

Abstract: The oligopeptidase tripeptidyl-peptidase II (TPP II) is upregulated Burkitt's lymphoma (BL) cells that overexpress the c-myc proto-oncogene and is required for their growth and survival. Here we show that overexpression of TPP II induces accelerated growth and resistance to apoptosis in human embryonic kidney 293 cells. This correlates with the appearance of multiple chromosomal aberrations, numerical and structural centrosome abnormalities, and multipolar cell divisions. Similar mitotic aberrations were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 36 publications
7
32
0
Order By: Relevance
“…However, other roles of TPPII may also exist, which may be unrelated to protein turnover. TPPII regulates transduction of apoptotic signals as well as centrosome homeostasis by unclear mechanisms (21,(27)(28)(29). We here found that the expression of TPPII is controlled by mTOR and that TPPII is rapidly translocated into the nucleus in response to g-irradiation.…”
Section: Introductionmentioning
confidence: 65%
“…However, other roles of TPPII may also exist, which may be unrelated to protein turnover. TPPII regulates transduction of apoptotic signals as well as centrosome homeostasis by unclear mechanisms (21,(27)(28)(29). We here found that the expression of TPPII is controlled by mTOR and that TPPII is rapidly translocated into the nucleus in response to g-irradiation.…”
Section: Introductionmentioning
confidence: 65%
“…Due to low endogenous TPPII expression and high transfection efficiencies, the human embryonic kidney cell line (HEK293) was chosen. Transient rather than stable overexpression of TPPII was performed because TPPII has been reported to disturb mitotic fidelity [20]. Because of restriction element incompatibility, the HEK293 cells were stably transfected with an expression construct encoding the H-2D b restriction element (named HEK-D b ) (Fig.…”
Section: Tppii Overexpression Does Not Increase the Presentation Of Lmentioning
confidence: 99%
“…The human papillomavirus type 16 E7 oncoprotein (HPV16 E7) induces centrosome duplication errors in primary human diploid epithelial cells (Duensing et al, 2000) through a CDK2-dependent mechanism . Similarly, the c-Myc oncogene has been linked to induction of centrosome abnormalities (Duensing et al, 2003;Stavropoulou et al, 2005). U2OS-C cells were transiently transfected with expression vectors encoding HA-tagged HPV16 E7 or c-Myc.…”
Section: S5a Expression Does Not Affect Induction Of Centrosome Abnormentioning
confidence: 99%